A new kind of sensor array for measuring spatial coherence of surface pressure on a car's side window - Gabriel, Christoph; Müller, Stefan; Ullrich, F.; Lerch, Reinhard (Journal of Sound and Vibration, 2014)
The mechanical behavior of a car's side window and the resulting acoustic radiation into the cabin is mainly affected by the spatial coherence of the surface pressure exciting the glass plate. The surface pressure is a superposition of hydrodynamic and acoustic pressure whose levels differ by 2 or 3 orders of magnitude. To gain information about the coherence characteristics of the surface pressure and to separate its hydrodynamic and acoustic components, a measurement of high spatial resolution is needed. For that reason a novel pressure transducer array with a minimum distance between two adjacent measurement points of only 2 mm was developed. The pressure transducers of the array are arranged sparsely on a grid while all possible distances between the spots on the grid are covered. Due to this minimization of distance redundancy, the amount of microphones could be reduced from 1849 to 92 representing a virtual array of 43 x 43 measurement positions. A Nyquist wavenumber of 250 1/m and a resolution of 11.9 1/m using a sensor area of only 52 x 52 mm(2) were achieved. Because of its small dimensions, this array allows for measurements at various test areas on the side window, which is a major improvement compared to former investigations. For the measurements conventional MEMS microphones are applied. It is shown that the used microphones are suitable for the requisite, even if operating in saturation. Hence, the existence of acoustic loads on the side window and the position-dependent spatial coherence of the surface pressure can be studied. Measurements using the sensor array are carried out in the anechoic wind tunnel to validate the methodology. Results of the separation between hydrodynamic and acoustic pressure as well as the identification of coherence properties are presented. (C) 2013 Elsevier Ltd. All rights reserved.